Solving Complex Social Problems Through Policy Integration. The Case of the National Crusade Against Hunger in Mexico - Cejudo, Guillermo M.; Michel, Cynthia L. (Revista del CLAD Reforma y Democracia, 2015)
In recent years, a practical concern (followed by a theoretical discussion) has emerged regarding the fragmentation of government action, governments’ inability to comprehensively address public problems or the increasing complexity of public issues (wicked problems) that make difficult for a single agency to solve them. How could a government address a complex problem with fragmented interventions? Different governments had tried to do it by implementing coordination strategies that aim at being comprehensive. In Mexico, the federal government recently designed the National Crusade against Hunger, which is a strategy to combat extreme food poverty suffered by people in the poorest municipalities in the country. It is a response to a social policy composed by programs with different purposes and target populations that has become more complex. It is a strategy that does not imply additional economic resources, new administrative structures or new programs. Achieving the National Crusade objectives entails the coordination of social programs within the federal government and among the federal, state and municipal agencies. In this paper, we argue that the fragmentation of social policy in Mexico is a result of the lack of coherence among a growing number of social programs, and the absence of management tools that would allow integrated policy decisions. We show that the National Crusade attempts to solve this problem from three different dimensions: the coherence between programs, the coordination of decision structures and administrative processes, and the integration of the governmental action. After a brief theoretical discussion, we show that the Crusade’s design addresses the fragmentation of government’s action. However, it fails to overcome the disarticulating effect of operating rules and routines that guide the action of officials towards particularistic goals.